Becoming Teachers for Social Justice: Raising Critical Consciousness. Issue 1 (4th March 2019) - Styslinger, Mary E.; Stowe, Jennifer; Walker, Nicole; Hyatt Hostetler, Kayla
Abstract: This article shares processes and practices which foster students' critical consciousness. Critical consciousness, the core of social justice teaching, is a heightened awareness of the world and the power structures that shape it. Teachers can become forces for equity and change by: challenging students to reflect critically on their beliefs and the sources of these beliefs; using text to guide students to look outwards and discover the perspectives and challenges of others; selecting texts purposefully to heighten student awareness of issues of power and equity; teaching students to read texts critically, listening carefully for the points of view of others often ignored or silenced; creating space for dialogue beyond text; and finally, making the world their classroom, blurring the boundary between schools and communities as students research the world and take steps toward change in ways that recognize and re-value our common humanity. Becoming teachers for social justice entails moving students through intentional processes and practices to foster critical consciousness in the hope of effecting change.